Migration, Identity and Proleptic Dynamism - Tia, Daniel (Advances in Social Sciences Research Journal, 2023)
Migration is far from being a recent phenomenon. Nor is it the prerogative of the twenty-first century. Wherever there are human beings, mobility emerges and human history provides various reasons, which justify the presence of a given community from one particular geographic region in another. Names, such as melting pot, salad bowl, and tossed salad are attributed to the United States, for its sociocultural construction was made of heterogeneous migratory flows. Those respective waves represent an undeniable driving force in American cultural and economic development. Like America, all other human societies have an experience of migration, but to varying degrees. Political instability, colonial influences, poverty, and armed conflict are the main factors of such an exodus. Individuals migrate to other spaces either to acquire social security or to improve their socioeconomic situation. In essence, migration creates the conditions for the construction of a futuristic identity whose effective achievement requires the acquisition of a stable and well-paid job. The more the world population increases, the more the migration scourge grows. The second half of the twentieth century and the first half of the current one are two periods in which the rate of migrants in Western societies seems to have reached a peak. Chronologically, the novels under consideration substantiate how the aforementioned periods remain paramount in terms of displacement. This work will therefore examine the issue of that futuristic identity, its related features and the conditions, which make it possible in Brown Girl, Brownstones and Americanah. Through the lens of the comparatistic perspective two points will be deciphered, inter alia "modalities of the migrants’ idyllic universe" and "impacts of hybrid identity."